2019
DOI: 10.1007/978-3-030-32040-9_32
|View full text |Cite
|
Sign up to set email alerts
|

Automated Spinal Midline Delineation on Biplanar X-Rays Using Mask R-CNN

Abstract: Manually annotating medical images with few landmarks to initialize 3D shape models is a common practice. For instance, when reconstructing the 3D spine from biplanar X-rays, the spinal midline, passing through vertebrae body centers (VBCs) and endplate midpoints, is required. This paper presents an automated spinal midline delineation method on frontal and sagittal views by using Mask R-CNN. The network detects all vertebrae from C7 to L5, followed by vertebrae segmentation and classification at the same time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…The current instance segmentation network mainly adds a Mask branch to the object detection network, such as Mask R-CNN [ 12 ], Blend Mask [ 13 ], and Hybrid Task Cascade [ 14 ]. Instance segmentation is applied to segment lung fields, heart, clavicles, and ribs in chest radiographs [ 38 , 39 ]; pelvis [ 40 ]; delineate spinal midline [ 41 ]; and to identify unknown bodies by tooth [ 42 ].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The current instance segmentation network mainly adds a Mask branch to the object detection network, such as Mask R-CNN [ 12 ], Blend Mask [ 13 ], and Hybrid Task Cascade [ 14 ]. Instance segmentation is applied to segment lung fields, heart, clavicles, and ribs in chest radiographs [ 38 , 39 ]; pelvis [ 40 ]; delineate spinal midline [ 41 ]; and to identify unknown bodies by tooth [ 42 ].…”
Section: Related Workmentioning
confidence: 99%
“…There are some papers comparing the performance of semantic segmentation and instance segmentation. The work in [ 41 ] finds that Mask R-CNN has higher accuracy in pelvis segmentation than U-Net. The work in [ 43 ] illustrates that instance segmentation methods are superior to semantic segmentation in tooth segmentation tasks.…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, the publication of several papers which used machine learning methods to automatically or semiautomatically extract parameters from biplanar radiographs of the spine (Galbusera et al, 2019;Gajny et al, 2019;Vergari et al, 2019;Aubert et al, 2019;Zhang and Li, 2019;Yang et al, 2019) demonstrated the rising interest in the topic and these novel techniques, as well as the need for automatizing a manual process which is time-consuming and relatively user-dependent (Somoskeöy et al, 2012;Bagheri et al, 2018). Our own deep learning tool (Galbusera et al, 2019) proved to be able to perform a fully automated 3D reconstruction of the spine shape as well as to estimate quantities such as spinopelvic parameters, kyphosis and lordosis angles, and coronal Cobb angle with perceptually convincing outcomes for a wide range of clinical scenarios including mild and severe deformities.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, applications of machine learning are not limited to radiographs but also extend to computerized tomography [13] and magnetic resonance imaging [14,15]. ment anatomical landmarks [2,3,6,7], the full geometry of the spine [8,9] or specific geometrical parameters, such as Cobb angle [10], lumbar lordosis [11] and sagittal verti-However, to the best of our knowledge, no work has been done to automatically detect scoliosis treatment (brace, implant or lack thereof) in postero-anterior radiographs. This information is of value either to develop automatic radiographic analysis tools, but it is usually not available in radiographs' DICOM metadata.…”
Section: Introductionmentioning
confidence: 99%